Delaying the inevitable: A political economy approach to currency defenses and depreciation - Walter, Stefanie; Willett, Thomas D. (Review of international political economy, 2012)
When faced with speculative pressure on their currencies, policymakers often delay devaluations by spending billions of dollars in defense of a given exchange rate peg, only to succumb and devalue their currency later on. Using a political economy approach we argue that the interaction of distributional concerns, cognitive limitations, time-consistency problems, and institutional structures can keep governments from implementing the economically optimal policy response. We argue that distributional concerns often lead to a ‘bias’ in favor of currency defense as long as market pressures are mild. The political incentives to initially delay devaluations can be exacerbated by institutions that either increase the size of interest groups vulnerable to depreciation or give policymakers incentives to adopt a short time-horizon. Once market pressure becomes strong, however, the politically salient alternative to not depreciating becomes raising interest rates rather than just running down reserves. This acts as a wake-up call that changes perceptions of the underlying distributional considerations and hence the political trade-off between the costs and benefits of an exchange rate defense. As the coalition of devaluation-proponents grows, the likelihood of a devaluation increases. We illustrate our argument by discussing the salient distributional issues and their interaction with domestic institutions in four brief case studies.
Published online: 11 Nov 2010
Gesehen am 12.02.2019